Utility of a simplified [18F] sodium fluoride PET imaging method to quantify bone metabolic flux for a wide range of clinical applications - Puri, Tanuj; Frost, Michelle L.; Moore, Amelia E. B.; Choudhury, Ananya; Vinjamuri, Sobhan; Mahajan, Abhishek; Fynbo, Claire; Vrist, Marie; Theil, Jørn; Kairemo, Kalevi; Wong, James; Zaidi, Habib; et al. (Frontiers in Endocrinology, 2023)
We review the rationale, methodology, and clinical utility of quantitative [18F] sodium fluoride ([18F]NaF) positron emission tomography-computed tomography (PET-CT) imaging to measure bone metabolic flux (Ki, also known as bone plasma clearance), a measurement indicative of the local rate of bone formation at the chosen region of interest. We review the bone remodelling cycle and explain what aspects of bone remodelling are addressed by [18F]NaF PET-CT. We explain how the technique works, what measurements are involved, and what makes [18F]NaF PET-CT a useful tool for the study of bone remodelling. We discuss how these measurements can be simplified without loss of accuracy to make the technique more accessible. Finally, we briefly review some key clinical applications and discuss the potential for future developments. We hope that the simplified method described here will assist in promoting the wider use of the technique.